Sports medicine - Fu, Freddie H; Lesniak, Bryson P (Wolters Kluwer, 2020)
This publication presents an overview of current pathology and treatment in the field of sports medicine and focuses on the surgical treatment of musculoskeletal injuries. Intended for professionals.
Master techniques in orthopaedic surgery
Keywords: ortopedické výkony; Musculoskeletal System; ortopedie; muskuloskeletální systém; sportovní úrazy; chirurgie; Orthopedic Procedures; tělovýchovné lékařství; Athletic Injuries